A study of quality of life among elderly and its relationship with physical and mental activity - Ibrahim, Amirah Fatin; Mohd Fauz, Siti Nor Farisya Nadia; Rosnani, Sarkarsi; Muda, Siti Mariam (Community Health Society Malaysia (CHSM), 2017)
Background: Aging will cause loss of physical and mental function, loss of family and also loss of spouse. These type of loses gradually affect quality of life among elderly. Therefore, it is important to increase awareness among people in the community to understand about the benefits of doing physical activities regularly.Materials and Methods: The aim of study is to assess whether physical and mental activity may improve the quality of life among elderly. A cross sectional study using a convenience sampling was conducted on 380 elderly aged 60 years and above in Kuantan, Pahang. The instruments used in this study were WHOQOL-BREF and GPAQ. The descriptive analysis and MannWhitney test were carried out.Result: There is zero number of respondents classified under high level of physical activity. A total number of 23 respondents were group among medium level and the rest were having low level of physical activity. There was no association between psychological healths; social relationship and environment domain as p-value for the test were ≥0.05 while the p-value for physical domain was ≤0.05. There was also no association between the mental activity and quality of life. It also identified no association between physical activity or mental activity and quality of life.Conclusion: Majority of the elderly had low level of physical activity, however those engaged in medium level of physical activity has a significantly higher level of quality of life. We identify the findings benefits to inform health care providers in emphasizing their health advice towards keeping the elderly physically active to maintain an optimal quality of life and healthy aging.